Improving access to imaging availability in otology clinic. Issue 1 (16th June 2022) - McLeod, Megan; Cass, Nathan; Bennett, Marc
Abstract: Rationale: Radiologic imaging is an essential component in the workup of many patients with neuro‐otologic conditions. However, patients often present for consultation with a neurotologist without the imaging that they have already undergone as part of their workup by a referring clinician. This disconnect causes frustration for clinicians and possible delays in care for patients. Anecdotally, clinicians felt that patients who had contact with clinic coordinators before their appointment were more likely to have their prior imaging available for review at the time of their initial consultation. Aims and Objectives: We aimed to increase the rate at which new patients brought their prior imaging to their initial consultation to at least 80% by improving previsit communication with patients and referring providers. Methods: Key stakeholders identified pain points in the flow of information from patients' outside facility workups. We then used the Plan‐Do‐Study‐Act quality improvement framework to develop, implement and iterate on two interventions intended to improve communication with patients, referring clinics and outside imaging centres. Chart review was used to assess the proportion of patients with imaging available for review at the time of initial consultation and a short satisfaction survey was sent to attending neurotologists in the pre and postintervention periods. Results: Before any interventions, 56.5% of typical new patients who reported having prior imaging had that imaging available for review at the time of their initial consultation. Following our interventions, this percentage increased to 73.5% and then 80.9% of new patients, respectively. Additionally, physicians reported improved satisfaction in several areas and spent less time reviewing imaging outside of clinic visits after our interventions. Conclusions: Improved communication and tracking of image receipt in clinics receiving many referrals saves physicians' time, reduces frustration and cuts down on the overall administrative burden following patients' appointments.